2003
DOI: 10.1002/jcp.10284
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transcriptional expression of DMT1 in the heart of rat

Abstract: Non-transferrin-bound iron (NTBI) overtaken by heart cells might be a key cause leading to iron-mediated injury in heart disorders. NTBI uptake by heart cells might be mediated by divalent metal transporter 1 (DMT1). The understanding of the role of DMT1 in heart iron metabolism is fundamental for elucidating the cause resulting in excessive iron in the heart. The study was to evaluate effects of age and dietary iron on DMT1 mRNA expression and protein synthesis in rat heart. DMT1 mRNA expression was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 41 publications
3
68
1
Order By: Relevance
“…The marked up-regulation of DMT1 implies that DMT1 plays an active role in iron acquisition by the heart, perhaps in concert with TfR1, which was similarly up-regulated. Similar to a previous study, 44 the higher DMT1 protein levels in irondeficient heart appear to result from post-transcriptional events because DMT1 mRNA levels were not higher.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The marked up-regulation of DMT1 implies that DMT1 plays an active role in iron acquisition by the heart, perhaps in concert with TfR1, which was similarly up-regulated. Similar to a previous study, 44 the higher DMT1 protein levels in irondeficient heart appear to result from post-transcriptional events because DMT1 mRNA levels were not higher.…”
supporting
confidence: 87%
“…Other studies have found that cardiac DMT1 levels were lower in iron-loaded animals than in controls. 44 Recently, Kumfu et al 43 reported that NTBI uptake by cardiomyocytes was unaffected when the iron uptake activity of DMT1 or TfR1 was blocked, indicating that DMT1 and TfR1 are not required for NTBI uptake into these cells. In iron-deficient heart, DMT1 levels were up-regulated 4-fold whereas ZIP14 levels were not affected.…”
mentioning
confidence: 99%
“…The authenticity of subcellular fractions was confirmed by Western blot analysis as previously described by (Ke et al, 2003), using primary monoclonal antibodies anti-nuclear core complex proteins-clone4 for nuclear fraction, anti-cytochrom-c oxidase for mitochondria, and antilactate dehydrogenase (H-subunit of LDH) clone HH-17 for cytoplasmic fraction (all were purchased from Sigma). A volume of protein extracts (40 µg) of total cell lysate, nuclei, mitochondria or cytoplasm was mixed with an equal volume of 2x sample buffer (0.125M Tris, 4% SDS, 20% glycerol, 0.02% 2-mercaptoethanol, and 0.01% bromophenol Blue), electrophoresed on a 4 -20% Tris-HCl linear gradient ready gels (Bio-Rad, Hercules, CA), and transferred to a PVDF membrane.…”
Section: Protein Separation and Verification Of Subcellular Fractionsmentioning
confidence: 99%
“…Western blot experiments were carried out as previously described (Ke et al, 2003). In short, cellular proteins were extracted in homogenization buffer containing 20 mM Tris, pH 7.5, 5 mM EGTA, 1% Triton X-100, 0.1% SDS, Protease Inhibitor Cocktail (Calbiochem, San Diego, CA).…”
Section: Western Blot Analysis Of Dmt1mentioning
confidence: 99%
“…DMT1 is most abundantly expressed in the duodenal epithelia. The expression of DMT1 in other cell types of nearly most of the organs has also been identified including erythrocytes, renal epithelial cells, cardiomyocytes and human placenta epithelia (Ferguson et al, 2001;Georgieff et al, 2000;Ke et al, 2003;Levy et al, 1999). In brain, DMT1 exists in neurons, cerebral capillary endothelial cells that constitute the blood-brain barrier (BBB) and the choroid plexus epithelial cells that comprise the blood-CSF barrier (BCB) (Burdo et al, 2001;Siddappa et al, 2003;Siddappa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%